Gold Nanoparticle-Based Detection of Low Molecular Weight AGEs from In Vitro Glycated Haemoglobin A0 Samples - A. Asha Madhavan; S. Juneja; P. Sen; R. Ghosh Moulick; J. Bhattacharya (Nanoscale Research Letters, 2018)
Abstract Protein glycation is a major biochemical event that takes place in the plasma of diabetic patients due to increased sugar levels. Extensive glycation leads to the formation of advanced glycation end products (AGEs) that is well known for having detrimental effects on diabetic patients. In the current work, we have glycated the physiologically important protein Haemoglobin A0 in vitro to study AGE formation and activity by using them as a template for gold nanoparticle (GNPs) synthesis. It was found that the surface plasmon resonance of synthesised GNPs showed high correlation with the extent of glycation. On fractionation, the glycated Haemoglobin A0 segregated into two distinct population of products, one consisting of proteinaceous, cross-linked larger fragments of Haemoglobin A0 and a second population of non-proteinaceous low molecular weight AGEs. Only low molecular weight AGEs contributed to synthesis of GNPs upon using the fractions as a template, substantiating the principle of proposed GNP-based assay. Owing to its physiological importance, AGEs can be used as a diagnostic means for diabetes and its associated complications. In this study, we have employed the high reactivity of AGEs for the development of a GNP-based novel colorimetric sensor to enable their detection. Our proposed GNP-based sensing could have high clinical significance in detecting diabetes and its associated complexities.